Antifungal Activities of Dimeric Sesquiterpenes, Shizukaols C and F, Isolated from Chloranthus japonicus Sieb - Kang, Tae Hoon; Lee, Yun Mi; Lee, Won Jung; Hwang, Eui Il; Park, Ki Duk; Choi, Gyang Ja; Moon, Jae Sun; Park, Ho-Yong; Kim, Sung Uk (Journal of microbiology and biotechnology, 2017)
Two dimeric sesquiterpenes were separated from Sieb. and identified as shizukaols C and F. They exhibited potent antifungal activities (MICs = 4-16 μg/ml) in vitro against various plant pathogenic fungi ( and ). Shizukaol C showed 88% and 91% protective activities in the greenhouse against (wheat leaf rust) and (tomato late blight), respectively, at 100 μg/ml; shizukaol F exhibited 93% antifungal activity against at the same concentration. Therefore, these compounds might serve as interesting candidates for effective antifungal agents.